KEJAHATAN DALAM PERDAGANGAN INTERNASIONAL: PERLINDUNGAN HUKUM PRODUK PERTANIAN LOKAL DALAM PASAR BEBAS - Ika Riswanti Putranti; Satwika Paramasatya (Fakultas Ekonomi Universitas Pekalongan, 2015)
Free trade zone established under international treaty instrument provides the facility specifically applies only to member States. Main facilities provided under such agreement covering reduction or even elimination of tariff barriers aimed to increase trade between members, yet it is vulnerable to trade crimes committed by third parties in order to take benefits. Origin fraud known as one of international trade crime that causes an injury for beneficiary countries. Regulatory instruments under international, regional, national, and regional dimensions, which aimed to prevent or to minimize the trade crimes become indispensable tools to avoid the losses of local producers.